Mário de Andrade’s Aesthetic and Ethical Consciousness (Research, Society and Development, 2019)
The objective of this article is to reconstruct and discuss the aesthetic and ethical reflections of the Brazilian modernist writer Mário de Andrade, to demonstrate the richness of his vision. The reading of some of his poems and critical texts, especially Prefácio Interessantíssimo and A escrava que não é Isaura, is compared to poems and reflections of other writers, besides some critics of his work, such as João Luiz Lafetá. Initially the equation “lyricism + art = poetry” is explored, visited by Mário de Andrade from various perspectives, resulting in the proposal of variants. Next, we observe the writer's anxieties regarding the artists’ options of political participation, especially the Brazilian modernists. The article concludes that, in his poetic work, Mário de Andrade materialized the proposals of his critical reflection.